Optical Solitons With M-Truncated and Beta Derivatives in Nonlinear Optics - Yusuf, Abdullahi; Inc, Mustafa; Baleanu, Dumitru (Frontiers in Physics, 2019)
This paper studies optical solitons with M-truncated and beta derivatives (BD) for the Complex Ginzburg-Landau equation (CGLE) with Kerr Law nonlinearity. Two well-known integration schemes which are generalized tanh method (GTM) and generalized Bernoulli sub-ODE method (GBM) are utilized to extract such optical soliton solutions. For the successful existence of the solutions, the constraints conditions have been presented. The discussion for the physical features of the obtained solutions is reported.